Stan i perspektywy rozwoju działalności korporacji transnarodowych w sektorze spożywczym Polski - Jaworska, Magdalena; Kozera, Cezary (State and Development of Transnational Corporations in Food Industry in Poland, 2006)
This paper presents the reasons of expansion of transnational corporations on Polish market, the biggest foreign investors in food industry and prospects of their development. Creation of a friendly system is indispensable for encouraging transnational corporations to invest in this sector based on stable economic policy and the improvement of infrastructure.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 335-340